A dark and twisted tide [large type] - Bolton, S. J. (Bolton, S. J. Lacey Flint novels, 2014)
"Now living in a houseboat on the River Thames, Lacey Flint is becoming a part of London's weird and wonderful riverboat community. But at dawn one hot summer morning, Lacey finds the body of a shrouded young woman in the river. She assumes it was chance--after all she's recently joined the marine policing unit--but further investigation leads her team to suspect it was deliberately left for her to find. She is no longer a detective, but as she begins to suspect someone is watching her very closely, she can't help but be drawn into the investigation. Award-winning author Sharon Bolton has once again crafted a tightly-plotted, utterly unpredicatable thriller around one of the most compelling characters in crime fiction today, enigmatic London police officer Lacey Flint"--